Analisis Perilaku Mahasiswa UMY dalam Penggunaan Website Sebagai Upaya untuk Meningkatkan Peringkat Webometrik - Fauziyah, Fauziyah (Jurnal Manajemen Bisnis, 2014)
Computer systems cannot improve organizational performance if they aren’t used optimally. To better predict, explain and increase user acceptance, we need to better understand why people are accept or reject a computer system. Reject often happened in the application of a new system. Once website UMY was introduced in Muhammadiyah University of Yogyakarta a few years ago, it’s not fully used actually by now. This research designs to explain the variables that influence behavior of the student to use website UMY. The simple TAM (Technology Acceptance Model) that contain 3 variables is used. The variables are Perceived Usefulness, Perceived Ease of Use and Actual Use. The results show that the three hypotheses are significantly proved. Both simultaneously and partially, Perceived Usefulness and Perceived Ease of Use are significantly influenced student’s Actual Use of website UMY. These indicate that the more actual use of website UMY the more succesfull the website.